EMOTIONAL LANGUAGE IN SELF-IMPROVEMENT BOOK BLURBS: A PSYCHOLINGUISTIC APPROACH TO AFFECTIVE READER ENGAGEMENT - Isabela Widya Nadita; Emy Sudarwati (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2026)
This study examines how emotional language functions as an affective strategy in self-improvement book blurbs and how it triggers reader engagement from a psycholinguistic perspective. Self-improvement books constitute a rapidly expanding genre, making their promotional blurbs a significant site for linguistic analysis. Blurbs function as affective instruments that mediate reader perception and engagement, yet the emotional language mechanisms operating within them remain undertheorised. Using a qualitative descriptive-analytic approach, the study integrates three complementary frameworks: Appraisal Theory (Martin & White, 2005), Halliday's Interpersonal Metafunction (Halliday & Matthiessen, 2014), and the Affect Infusion Model (Forgas, 1995). Six blurbs from Brianna Wiest's bestselling self-improvement books (2016–2025) were selected for genre consistency, publication range, and international recognition. The analysis reveals that emotional language is systematically constructed across three appraisal systems, namely Attitude, Engagement, and Graduation, forming a coherent affective architecture. These resources are strategically deployed through interpersonal choices of mood, pronoun, and modality to construct an affective writer-reader relationship. Emotional language appears to facilitate reader engagement through affective and evaluative processes, operating as a cognitive heuristic that shapes readers' decisions to engage with the text. This study contributes to discourse analysis by demonstrating how emotional language in self-improvement blurbs strategically constructs affective relationships that drive readers engagement.